Haemovigilance data on the use of methylene blue virally inactivated fresh frozen plasma with the Theraflex MB‐Plasma System in comparison to quarantine plasma: 11 years' experience. Issue 5 (29th September 2014) - Politis, C.; Kavallierou, L.; Hantziara, S.; Parara, M.; Zervou, E.; Katsarou, O.; Hatzitaki, M.; Fountouli, P.; Gioka, A.; Tzioura, K.; Koumarianos, S.; Asariotou, M.; et al.
SUMMARY Objectives/Background Haemovigilance is an effective tool for identifying adverse effects of blood components. We analyse cumulative haemovigilance data in order to compare the two secured therapeutic plasmas that have been in use for more than 11 years in Greece – methylene blue‐treated fresh frozen plasma (MB‐FFP) and quarantine fresh frozen plasma (Q‐FFP) – regarding safety and adverse events. Methods/Materials Data from the centralised active haemovigilance system of Greece for the period 2001–2011 were used to examine the association between FFP types and adverse events. Post‐transfusion information on infectious and non‐infectious adverse events was analysed. Events were examined by reaction type, severity and imputability to transfusion. Results The incidence of adverse events was higher with Q‐FFP (1:3620) than MB‐FFP (1 : 24 593) by a factor of 6·79 [95% confidence interval (CI) 2·52–27·8]. Allergic adverse events were also commoner with Q‐FFP (1 : 7489) than with MB‐FFP (1:24 593), by a factor of 3·28 (95% CI 1·17–13·7). All adverse reactions experienced by the MB plasma recipients were considered to be mild. Conclusion Haemovigilance over 11 years has demonstrated the long‐term safety of MB‐FFP in comparison to untreated quarantine FFP. In addition to lowering the adverse event rate, implementing the system on a national scale in at‐risk countries would presumably reduce the transmission of severe viral infections including emerging infectious diseases by transfusion.